FliL associates with the stator to support torque generation of the sodium‐driven polar flagellar motor of Vibrio. Issue 1 (17th July 2015) - Zhu, Shiwei; Kumar, Ananthanarayanan; Kojima, Seiji; Homma, Michio
Summary Flagellar motors generate torque to rotate flagellar filaments and drive bacterial cells. Each motor is composed of a rotor and many stators. The stator is a force‐generating complex that converts ion flux into torque. Previous reports have suggested that the membrane protein FliL is located near the stator and is involved in torque generation. We investigated the role of FliL in the sodium‐driven polar flagellar motor of Vibrio alginolyticus. Our results revealed that FliL is a cytoplasmic membrane protein and is located at the base of flagellum. The deletion of fliL did not affect the cell morphology or flagellation but resulted in a significant decrease of swimming speed, especially at a higher load thus suggesting that FliL is important for torque generation at high load conditions. Furthermore, the polar localization of the stator was decreased in a ΔfliL mutant, but the sodium‐dependent assembly of the stator complex was still retained. The polar localization of FliL was lost in the absence of the stator complex, indicating that FliL interacts directly or indirectly with the stator. Our results suggest that FliL is localized along with the stator in order to support the motor functioning for swimming at high load conditions by maintaining the stator assembly.